2010
DOI: 10.1287/isre.1100.0327
|View full text |Cite
|
Sign up to set email alerts
|

Research Commentary—The Digital Transformation of Healthcare: Current Status and the Road Ahead

Abstract: A s the United States expends extraordinary efforts toward the digitization of its health-care system, and as policy makers across the globe look to information technology (IT) as a means of making health-care systems safer, more affordable, and more accessible, a rare and remarkable opportunity has emerged for the information systems research community to leverage its in-depth knowledge to both advance theory and influence practice and policy. Although health IT (HIT) has tremendous potential to improve quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
412
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 743 publications
(474 citation statements)
references
References 78 publications
8
412
0
8
Order By: Relevance
“…wellbeing Digital transformation in healthcare seeks solutions to make healthcare safer, more affordable and more accessible, and has lately been a very rapidly growing area of research [1]. The expertise of medical professionals has made healthcare one of the first domains, to which new artificial intelligence technologies have been deployed, with varying levels of success.…”
Section: A Finding Opportunities For Ai In Health and Social Care Andmentioning
confidence: 99%
“…wellbeing Digital transformation in healthcare seeks solutions to make healthcare safer, more affordable and more accessible, and has lately been a very rapidly growing area of research [1]. The expertise of medical professionals has made healthcare one of the first domains, to which new artificial intelligence technologies have been deployed, with varying levels of success.…”
Section: A Finding Opportunities For Ai In Health and Social Care Andmentioning
confidence: 99%
“…On the macro-level, evaluating the impact of health IT is still much needed [1]. In addition, useful insights have to be generated by studying health IT at the micro-level [1] where Computerized Physician Order Entry (CPOE) has proven to be effective in increasing patient safety and reducing medication errors and costs [18].…”
Section: Design Of Hospital Information Systemsmentioning
confidence: 99%
“…In addition, useful insights have to be generated by studying health IT at the micro-level [1] where Computerized Physician Order Entry (CPOE) has proven to be effective in increasing patient safety and reducing medication errors and costs [18]. Factors such as functionality and ease of use can vary significantly across these type of systems [1].…”
Section: Design Of Hospital Information Systemsmentioning
confidence: 99%
“…The literature indicates physicians resist the technology due to productivity issues, workflow challenges, lack of support and other issues related to the mismatch between the technology and healthcare delivery process [1,3,4,12,19,21,24,26]. A recent study by Noteboom and Hafner [22] found that "technological upset" takes place when physicians do not unlearn their past behaviors in order to use technology.…”
Section: Theoretical Backgroundmentioning
confidence: 99%